Rancang Bangun Aplikasi Sistem Peminjaman Unit Multimedia Menggunakan Metode Waterfall - Ricki Sastra; Gugum Gumelar (INSANtek, 2021)
Abstract - The Multimedia Unit Loan System in an agency is vital. Where each agency will need various items or other inventory to run and encourage the event to run. Multimedia items that are needed only for a moment in an event must function properly so that the event can run smoothly. So far the lending process is still not optimal, borrowing is still carried out conventionally by recording using book media and has shortcomings because there are still some errors. And in the process of borrowing goods, communication errors often occur between employees and owners with customers, considering the number of goods owned is complicated to regulate the availability of units of goods. In addition, the data collection process for multimedia goods still uses forms to fill in data so that recording errors can occur during the borrowing process. With the application of the goods lending system designed using the Agile method. expected to support the process of inputting employee goods applications, procurement of goods, checking stock, and reports of incoming goods so that the process can run well